Rancang Bangun Remote Control Robot Lengan 6DOF Dengan Protokol ESP-NOW - Zebua, Nike Erni; Setyawan, Gogor C.; Lase, Kristian Juri Damai (STMIK Banjarbaru, 2024)
A robotic arm is one of the robotic applications that is increasingly developing in various industries. The robotic arm is designed and built with a remot control system using the ESP-Now communication protocol. This system aims to improve the efficiency and precision of controlling robotic arms, which are widely used in various industrial and research applications. The ESP-Now protocol is chosen for its advantages of low latency and minimal power consumption in short-range communication. The design process includes the creation of a mechanical model of the robotic arm, the development of hardware and software for the control system, as well as the integration and testing of the overall system. Test results show that the built-in remot control system can control the robotic arm with high precision and quick response as needed for operational requirements. Therefore, this system is expected to make a significant contribution to the field of automation and robotics and serve as a reference for further development of robotic control technology.Keywords: Robotic arm; 6DOF; microcontroller; ESP-Now; wireless control.Â AbstrakRobot lengan merupakan salah satu aplikasi robotik yang semakin berkembang di berbagai industri. Robot lengan dirancang dan dibangun dengan sistem kendali jarak jauh menggunakan protokol komunikasi ESP-Now. Sistem ini bertujuan untuk meningkatkan efisiensi dan presisi pengendalian lengan robot yang banyak digunakan dalam berbagai aplikasi industri dan penelitian. Protokol ESP-Now dipilih karena keunggulan latensi rendah dan konsumsi daya minimal dalam komunikasi jarak pendek. Proses perancangan meliputi pembuatan model mekanis lengan robot, pengembangan perangkat keras dan perangkat lunak sistem kendali, serta pengintegrasian dan pengujian keseluruhan sistem. Hasil pengujian menunjukkan bahwa sistem kendali jarak jauh bawaan dapat mengendalikan lengan robot dengan presisi tinggi dan respon cepat sesuai kebutuhan operasional. Oleh karena itu, sistem ini diharapkan dapat memberikan kontribusi yang signifikan di bidang otomasi dan robotika, serta menjadi acuan bagi pengembangan teknologi pengendalian robot lebih lanjut.Kata kunci:Â Robot lengan; 6DOF; mikrokontroler; ESP-NOW; pengendalian wirreless.